The impacts of ad skip option and ad time display on viewer response to in-stream video ads: the role of perceived control and reactance - Choi, Dongwon; Kim, Jooyoung (Internet research, 2022)
PurposeThe primary purpose of the current study was to examine how the presence of two digital ad features – an ad skip option and an ad time display, representing behavioral and cognitive control, respectively – might influence viewer response to in-stream video ads in terms of perceived control, reactance and advertising outcomes.Design/methodology/approachA 2 (Ad skip option: presence vs. absence) × 2 (Ad time display: presence vs absence) between-subjects experiment was conducted online with 217 participants recruited via Qualtrics.FindingsThe results of the online experiment show that the presence of the ad skip option and ad time display related to a higher level of perceived control, predicting lower ad intrusiveness and ad irritation and more favorable attitude toward the ad.Practical implicationsThe findings confirm that an ad skip option and an ad time display could minimize negative responses to in-stream video ads by increasing perceived control and reducing viewer reactance.Originality/valueThe findings provide empirical evidence that multiple dimensions of control features (i.e. behavioral and cognitive) can increase perceived control and strengthen its impact on advertising outcomes.